2018
DOI: 10.1097/inf.0000000000001962
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Extensively Drug-resistant Acinetobacter baumannii at a Children Hospital in Bolivia

Abstract: Acinetobacter baumannii causes serious hospital-acquired infections and has been positioned as a priority organism by the World Health Organization. This study includes 36 A. baumannii isolates from a children hospital recovered between March 2014 and May 2015 in Cochabamba. The majority of the isolates were recovered from blood cultures (n = 10, 31.3%) and respiratory samples (n = 11, 34.4%); 53% of the patients were younger than 1 month old. Most of these isolates (n = 30, 80.6%) were extremely drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…This study identified patterns of antimicrobial resistance in A. baumannii isolates at a tertiary care center in Honduras and found that nearly 50% came from its pediatric wards. This result concurs with studies from other countries (14,15) that found the pathogen was predominantly isolated in pediatric wards, especially pediatric ICUs. Notably, at the study hospital, 25% (n = 2) of the XDR isolates were from children compared to the findings of a recent study in Bolivia (15) where the rate was 8.3% (n = 3).…”
Section: Discussionsupporting
confidence: 92%
“…This study identified patterns of antimicrobial resistance in A. baumannii isolates at a tertiary care center in Honduras and found that nearly 50% came from its pediatric wards. This result concurs with studies from other countries (14,15) that found the pathogen was predominantly isolated in pediatric wards, especially pediatric ICUs. Notably, at the study hospital, 25% (n = 2) of the XDR isolates were from children compared to the findings of a recent study in Bolivia (15) where the rate was 8.3% (n = 3).…”
Section: Discussionsupporting
confidence: 92%
“…In A. baumannii, the bla OXA−23−like gene is associated with ISAba1, which contributes to its overexpression as well as its mobilization (Nigro and Hall, 2016). Tn2008 has previously been described in Bolivian A. baumannii isolates and this mirrors the spread of this structure among different ICs leading to a carbapenem-resistant phenotype (Nigro and Hall, 2016;Sennati et al, 2016;Chen et al, 2017;Ewers et al, 2017;Cerezales et al, 2018).…”
Section: Resultsmentioning
confidence: 95%
“…This resistance mechanism can be acquired by Gram-positive or Gram-negative bacteria [ 21 ]. One of the most known examples of antibiotic-modifying enzymes is β-lactamases [ 22 ]. These enzymes can hydrolyze and deactivate β-lactam drugs, the most widely used group of antimicrobial agents.…”
Section: Antimicrobial Resistance Mechanismsmentioning
confidence: 99%